Sistem Informasi Inventaris Peralatan Berbasis Web Pada Yayasan Pendidikan Islam Al-Azni - Muhammad Fatchan; Novi Sri Yuliani; Andri Firmansyah (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2022)
Inventory equipment is one of the facilities provided to support and support the process of teaching and learning activities for teachers at the Al-Azni Islamic Education Foundation. However, currently the management of inventory data is not well organized so that it affects the process of borrowing and returning inventory equipment, because it is still not computerized, that is, the borrower only needs to write data on borrowing and returning goods in a notebook, this can have an impact on the delay in the work process if a lot of goods are needed. borrowed and returned. and the risk of goods being lost or damaged without the origin of the last borrower who used it. The purpose of this thesis is to produce a web-based equipment inventory information system with PHP and MySQL. The test is carried out using the Black-box testing method. From the results of the study it can be concluded that the existence of a web-based inventory information system can accelerate data processing about the facilities and infrastructure owned by the agency, and also has the ease and accuracy of running the system at the Al-Azni Islamic Education Foundation